Escritório de gerenciamento de projetos: o caso sabesp no combate às perdas de água - Cianfanelli, Mário Manzini (2012)
This work demonstrates how the implantation of the evolutive process of the manager office of projects (PMO) was done in one of the Unit of Business of Basic Sanitation Company of São Paulo State, known as Sabesp, that was created to minimize the loss of water during its distribution. The methodology that was used to achieve this goal was the unique case study through a documental research that was complemented with interviews analyzed through an analyze of a content. The path to the establishment of the office was examined showing besides the barriers and facilities, the aspects related to the sponsors influence in the reduction of the losses program, the capacity of the organizational structure in the adoption of the project management and also of the PMO, the main attributions of the PMO and the perception of the interviewees in relation to the success that was obtained. The results show how the implementation allowed the organization improve the planning and the control of the projects activities, making it possible the integration between the departments involved in the efforts to solve the problems caused by the losses. This work concludes that with this implantation of the project management office it was possible to improve the planning and the control of the activities of the projects through a pattern methodology in managing projects that gave possibilities to create a new culture focusing in solving problems.